After-Hours Stock Prices and Post-Crash Hangovers. - Neumark, David; Tinsley, P A; Tosini, Suzanne (Journal of Finance, 1991)
After-hours pricing in foreign equity markets of multiple-listed U.S. securities appeared to be efficient in predicting New York prices in the weeks immediately following the October 1987 crash, but relatively uninformative in succeeding months. By contrast, daily changes in New York prices appear to be efficiently incorporated in after-hours trading on both the Tokyo and London exchanges throughout the sample period. This paper suggests that the asymmetry and temporal variations in cross-market correlations are consistent with rational investor behavior in equity markets with nonzero transaction costs and time-varying share price volatility.